PROBLEM AND PERSPECTIVE OF ISLAMIC MONETARY POLICY IN INDONESIA - Marsuki Marsuki (Jurnal Keuangan dan Perbankan, 2010)
This article would try to explicate several theoretical and practical concepts on the problems and prospectsof Islamic monetary policy in Indonesia using a critical analysis approach, in accordance with standardscientific references, and would be complemented with descriptions and examples of practice. From theseillustrations and analyses, it appeared that on one hand, Islamic monetary policy would find many difficultiesif implemented fully, considering that there were several fundamental obstacles that would have to besurmounted by such an implementation, primarily the fact that Indonesian Constitution (UUD 1945) was notbased on Islamic law or syariah. On the other hand, despite problems and challenges, the existing conditionwas still open for the possibility for partial implementation of Islamic monetary policy. It was because therewere several conditions which were amenable for an implementation, for instance the facts that majority ofIndonesian population was Muslim, the increasing acceptance of the public for the advantages of Islamicmonetary and financial system, and increasing support by stakeholders of the banking system, especiallythe Indonesian central bank (BI). Moreover, there were facts about financial institutions and existingsyariah banking institutions.